MEKANISME KINERJA KEUANGAN UNTUK MENGATASI KREDIT MACET PT BPR BKK TEMANGGUNG (PERSERODA) KC CANDIROTO - Bilqisti, Amarani Robbi; Putri, Sanrina Indriati (Mount Hope Management International Journal, 2024)
The purpose of this study is to determine how financial performance in overcoming bad debts at PT BPR BKK Temanggung KC Candiroto. Financial performance with bad debts are two things that greatly influence each other. The data analysis method for this study is a qualitative method, namely by systematically describing data from facts obtained through interviews and documentation at PT BPR BKK Temanggung KC Candiroto. The phenomenon of bad debts is the provision of credit that has a high risk for the survival of banking if the provision of credit is not managed properly. To avoidproblematic credit, credit management is needed which is good credit management. (Mulyadi, 2016). This study uses a qualitative approach and conducts a comprehensive data analysis of a problem. The sources of this research are primary data and secondary data obtained from interviews, observations, and documentation.